Molecular Cloning, Expression, Purification, and Functional Characterization of Dammarenediol Synthase from Panax ginseng. (30th December 2012) - Hu, Wei; Liu, Ning; Tian, Yuhua; Zhang, Lianxue
Abstract : The objective of this study is to clone and charecterize the expression of dammarenediol synthase gene and then to determine the relationship between the expression of dammarenediol synthase gene that is involved in the ginsenoside biosynthetic pathway and the ginsenoside content. A cDNA phage library was constructed from a five-year-old ginseng root. The cDNA library was screened for the dammarenediol synthase gene by using its specific primers. It was further cloned and expressed in pET-30a vector. The recombinant plasmid pET-30a-DS was expressed in Rosetta E. coli . The recombinant DS protein was purified by affinity chromatography. The production of dammarenediol was detected by liquid chromatography-mass spectrometry (LC-MS). Results showed that dammarenediol synthase gene was cloned from the cDNA library and was expressed in Rosetta E. coli and the SDS-PAGE analysis showed the presence of purified DS protein. LS-MS showed the activity of DS protein, as the protein content increases the dammarenediol increases. Our results indicate that the recombinant dammarenediol synthase protein could increase the production of dammarenediol and the expression of DS played a vital role in the biosynthesis of ginsenosides in P. ginseng .